2020
DOI: 10.18488/journal.62.2020.76.387.400
|View full text |Cite
|
Sign up to set email alerts
|

Risk Management and Shareholders’ Wealth Maximization

Abstract: Risks are fundamentally part of business operational models; it cannot be completely eliminated and if not efficiently managed could result to loss of value. Wealth creation could only take place when the prevailing financial risks in the banking sectors are identified and carefully handled. An expost-facto study of 100 firm-year observations was conducted using ten listed Deposit Money banks in Nigeria for a period of 10 years from 2009 to 2018. The results of the multiple regression analysis carried out reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Kalu, Shieler, and Amu (2018) indicated that monitoring and mitigating credit risk was not statistically associated with company performance. Ogundajo et al (2020) established that credit risk and operating efficiency risk both impact market value negatively.…”
Section: Credit Risk and Shareholder Wealthmentioning
confidence: 99%
“…Kalu, Shieler, and Amu (2018) indicated that monitoring and mitigating credit risk was not statistically associated with company performance. Ogundajo et al (2020) established that credit risk and operating efficiency risk both impact market value negatively.…”
Section: Credit Risk and Shareholder Wealthmentioning
confidence: 99%